Sustainability-oriented assessment of external thermal insulation composite systems: A case study from Poland. Issue 1 (1st January 2021) - Michałowski, Bartosz; Michalak, Jacek
Abstract: External Thermal Insulation Composite System (ETICS) technology is commonly used to insulate buildings to increase the energy efficiency of external building envelopes. The ETICS is a construction product whose use has a significant impact on the environment and which itself is subject to an environmental impact assessment. The paper presents the impact of producing all ETICS components on the natural environment using the life cycle assessment method. The data used in the calculations, related to 2012 and 2017 real production, were obtained from the externally verified inventory from five manufacturing plants located in different regions of Poland. Life Cycle Assessment (LCA) of the examined products covered modules from A1 to A3 (Cradle-to-Gate) according to EN 15804 standard. That includes raw materials extraction, processing of secondary material, transport to the manufacturer, and production up to the finished, packed product at the factory gate. In the period of 2012–2017, the negative impact on the natural environment for most environmental indicators for the entire ETICS (all of its components), has been significantly reduced. For the first time, changes of such indicators as GWP, ODP, AP, EP, POCP, ADP, ADP, PERT, PENRT over 5 years period for ETICS have been presented.